Bacteriological Evaluation of Well Water Samples from Selected Community Markets in Ijebu-Remo Axis of Ogun State - Okunye, Olufemi Lionel; Adegboyega, Idowu Philip; Teniola, Kolade Titilayo (Nigerian Journal of Pharmaceutical and Applied Science Research, 2019)
The quality of portable water and treatment of water borne diseases are critical public health issue. This study was carried out in Ijebu-Remo communities-axis of Ogun State to evaluate the bacteriological and physicochemical quality of in-situ community market well water for the presence of coliforms and other associated potential pathogens. A total of 24 wells from selected 6 market locations were examined. They were found to be laden with coliforms, Pseudomonas and Klebsiella in varying percentage. The potential hydrogen concentrations of the 24 wells examined were acidic with the exception of 2 wells with a pH 7. The total viable count varied between 7×106 to 47.5 ×106. Though the regressive analysis to determine the significance of the extrinsic and intrinsic values of the sampled water extends beyond the P-values?0.5, the total viable count from the 24 well water sampled were grossly contaminated. Therefore, the water is unsafe for drinking to avoid water borne infection of unpredictable magnitudes.